The 2D Barcodes Identify the Workpieces by using Microcontroller Interface between Image Processing and PLC Machine - SINGHATA, Napassadol (Walailak journal of science and technology, 2021)
This paper focuses on 3 main subjects; the first is the presentation and implementation of a PLC concept as a core component to control the system in the industry. The next subject of this work involves some tests to detect 2D barcodes with a web camera on 5 similar workpieces. It is difficult to classify and detect 2D barcodes since they are small about a size of 0.5×0.5 cm2 patterned squares. The last part of the paper presents the implementation of a technique by using a microcontroller to link between a vision system and PLC. This method can be used in an old type of PLC without an additional equipment in the PLC, which can be connected to various types of cameras. The results of the system test show that the vision system can operate in the automatic classifying machine of the PLC controller. The machine vision can classify similar workpieces by using small 2D barcodes with image processing methods. The workpieces are stored in the correct position of 5 boxes in the storage compartment. This method of using a microcontroller interface with image processing and the PLC was successful. HIGHLIGHTS Web camera sensor read 2D barcodes Decoding 2D barcode and transform to digital signal Incorporating image processing into PLC system by using microcontroller and relay Transform signal into PLC processing to classifying the workpieces GRAPHICAL ABSTRACT